The Role Of The Mother Tongue And Translation In Efl Classes - Sara Moussedek; Hicham Benmokhtari (Al-Lisaniyyat, 2019)
Learning is a cumulative process that is shaped by past experiences. Language learning in particular puts in focus learners’ level, age, and background. Thus, acquired habits from the mother tongue will be a point of departure which builds up new learned habits. So transfer from old to new situations is necessary in knowledge construction. It is then the aim of the current study to enquire the usefulness of transfer as a learning strategy in the mundane EFL practices. For instance, contrastive analysis assumed that the native language is the driving force of second language learning. Besides, several other views are provided as proofs on the germane role the native language and translation play in ELT courses. An emphasis on further research on the importance of the mother tongue in second language learning concludes the discussions in this article.